Effects of Different Forms of Concept-Map Representation on Nursing Students' Critical Thinking Performances - Chin-Yuan Lai; Sheng-Mei Chen; Cheng-Chih Wu (National Taipei University of Education, 2015)
Representation is important for problem solving. This study examined the effects of different forms of concept maps on nursing students' performances of conceptualizing psychiatric patients' problems. A quasi-experimental research design was adopted to investigate the effects. The participants were two classes of fourth-year students who were enrolled in a psychiatric nursing course in a nursing college. One class with 48 students served as the experimental group, and used web-based concepts map to represent patients' problem. The other class with 50 students served as the control group, and used the traditional hierarchical concept mapping method. The results indicated that the concept maps drawn by the experimental group showed more nursing problem, supporting evidence, and relationships between nursing problems than those drawn by the control group. The web-based concept maps helped expand students' thinking and promoted their causality reasoning. Different concept-map representation tools affected the process of students' problem solving. The experimental learning activities promoted students' understanding of concepts and ways of psychiatric patients' care taking. To understand the effects of other types of concept maps, future research may guide students in using different forms of concept maps throughout the stages of nursing process.